AVANÇOS E DESAFIOS NO DIAGNÓSTICO E TRATAMENTO DE CARDIOPATIAS CONGÊNITAS: UMA REVISÃO SISTEMÁTICA - Maximiliano, João Victor Vasconcelos Tavares; Figueiredo, Sarah Antunes; Bandeira, Gabriela Travassos; Vasconcelos, Laynny da Trindade; Silva, Joseane da; Barreto, Vitor Lins Acioli; Santos, João Mario Berto dos; Rocha, Aimê Cândida; Carvalho, Renan Araújo de; Laurindo, João Victor; Barros, Júlio César Soares; Silva , Antonia Cardoso (Periódicos Brasil. Pesquisa Científica, 2024)
Congenital heart disease is a complex medical condition that affects the development of the heart before birth. These cardiac anomalies are among the most common congenital defects, contributing significantly to infant morbidity and mortality worldwide. To conduct this systematic review on congenital heart diseases, the platform selected for article search was Google Scholar, one of the largest and most comprehensive databases of scientific literature in the biomedical field. The search period was defined from 2018 to 2024, aiming to include recent studies reflecting the latest advances in the diagnosis and treatment of congenital heart diseases. Ultimately, the treatment of congenital heart diseases requires a multidisciplinary, individualized, and constantly evolving approach. With the advancement of medical technology and increased understanding of the underlying pathophysiology, it is expected that new therapies and approaches will continue to improve outcomes for patients affected by these complex cardiac conditions.